Toward an integrated reporting framework in higher education institutions: evidence from a public university - Aras, Guler; Kutlu Furtuna, Ozlem; Hacioglu Kazak, Evrim (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose The main purpose of this paper is to evaluate to what extent a public university, named Yildiz Technical University, integrated report provides disclosure on International Integrated Reporting Council (IIRC) content elements, suggesting the presence of integrated thinking, and whether higher education institutions'(HEIs) characteristics could affect the level of disclosure on that framework. Additionally, the purpose of this paper is to identify whether the Yildiz Technical University follows the IIRC framework and how integrated reporting can enhance the value creation for HEIs' stakeholders in the context of voluntary reporting. Design/methodology/approach To conduct integrated reporting framework in HEIs specifically from a public university perspective, this paper has used a case study approach. Research data have been triangulated through interviews, questionnaires and finally, documents and archival records. Findings This paper gives insights into the reporting practices from a public institution, specifically from HEIs. Delivering high-quality services in an economically, environmentally and socially sustainable manner is significant to public accountability and transparency. The Yildiz Technical University has been the best example in disclosing non-financial information to its stakeholders and enhancing the accountability tool. Practical implications This paper can be a leading practice and can be considered as an integrated reporting framework for HEIs willing to follow the same path. Originality/value To the best of the authors' knowledge, this paper is the first to investigate the integrated reporting framework in a developing country, under HEIs and specifically for a public university.
Keywords: Integrated reporting; HEIs; Institutional theory; Signaling theory; Case study; Turkey; Higher education institutions; SUSTAINABILITY; Science & Technology - Other Topics; Education & Educational Research